2021
DOI: 10.1007/s40200-021-00777-4
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase 4 (DPP4) inhibitor and outcome from coronavirus disease 2019 (COVID-19) in diabetic patients: a systematic review, meta-analysis, and meta-regression

Abstract: Background One of the drugs which is commonly used in diabetic patients is Dipeptidyl Peptidase-4 (DPP-4) inhibitor. Currently, the association between DPP-4 inhibitor and coronavirus disease 2019 (COVID-19) outcome is not yet established. This study aims to analyze the potential association between DPP-4 inhibitor and the composite poor outcome of COVID-19. Methods We systematically searched the PubMed and Europe PMC database using specific keywords related to our aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 31 publications
0
29
1
1
Order By: Relevance
“…One meta-analysis of six studies (heterogeneity [ I 2 ]: 54%) and another of seven studies ( I 2 : 55%) published in December 2020 and January 2021, respectively, revealed no significant difference in the risk for the development of a fatal or severe course of illness with the use of DPP-4is in patients with COVID-19 [ 31 , 32 ]. Two subsequent meta-analyses with very low heterogeneity, published in February 2021 and March 2021 and included nine and ten studies, respectively, came to similar conclusions [ 33 , 34 ], with the exception of some benefits of in-hospital use of DPP-4is. More recently, Rakhmat et al published a meta-analysis of nine studies and reported that taking DPP-4is was associated with lower mortality in COVID-19 patients with diabetes mellitus [ 35 ].…”
Section: Discussionmentioning
confidence: 75%
“…One meta-analysis of six studies (heterogeneity [ I 2 ]: 54%) and another of seven studies ( I 2 : 55%) published in December 2020 and January 2021, respectively, revealed no significant difference in the risk for the development of a fatal or severe course of illness with the use of DPP-4is in patients with COVID-19 [ 31 , 32 ]. Two subsequent meta-analyses with very low heterogeneity, published in February 2021 and March 2021 and included nine and ten studies, respectively, came to similar conclusions [ 33 , 34 ], with the exception of some benefits of in-hospital use of DPP-4is. More recently, Rakhmat et al published a meta-analysis of nine studies and reported that taking DPP-4is was associated with lower mortality in COVID-19 patients with diabetes mellitus [ 35 ].…”
Section: Discussionmentioning
confidence: 75%
“…[2][3][4][5][6][7] Several therapies had been proposed to control and manage these conditions. [8][9][10][11][12][13][14] Recently the use of GLP1-RA, as one alternative to treat DM patients, had shown promising effect to reduce excessive inflammation-induced acute lung injury and improving Covid-19 outcome. [15] In addition to stimulating postprandial insulin secretion, GLP1-RA also seems to have beneficial properties such antiinflammatory, anti-obesogenic, pulmonary protective effects and gut microbiome modulating effects.…”
Section: Introductionmentioning
confidence: 99%
“…Good glucose control has been demonstrated to exert a protective effect in the context of the development and outcomes of COVID-19 (3)(4)(5), and strict glucose management on admission for COVID-19 cases has been suggested regardless of diabetes status (6). The role of glycemic control strategies, such as several antidiabetic drugs including metformin and DPP-4 inhibitors in the efficacy and safety of COVID-19 and diabetes has been established (7,8). However, whether insulin injection has some effect on the development of COVID-19 remains inconsistent.…”
Section: Introductionmentioning
confidence: 99%